Role of type I interferons in the activation of autoreactive B cells - Kiefer, Kerstin; Oropallo, Michael A; Cancro, Michael P; Marshak‐Rothstein, Ann (Immunology and cell biology, 2012)
Type I interferons (IFNs) are a family of cytokines involved in the defense against viral infections that play a key role in the activation of both the innate and adaptive immune system. IFNs both directly and indirectly enhance the capacity of B lymphocytes to respond to viral challenge and produce cytotoxic and neutralizing antibodies. However, prolonged type I IFN exposure is not always beneficial to the host. If not regulated properly IFN can drive autoantibody production as well as other parameters of systemic autoimmune disease. Type I IFNs impact B‐cell function through a variety of mechanisms, including effects on receptor engagement, Toll‐like receptor expression, cell migration, antigen presentation, cytokine responsiveness, cytokine production, survival, differentiation and class‐switch recombination. Type I IFNs are also cytotoxic for a variety of cell types and thereby contribute to the accumulation of cell debris that serves as a potential source for autoantigens. Type I IFN engagement of a variety of accessory cells further promotes B‐cell survival and activation, as exemplified by the capacity of type I IFNs to increase the level of B‐cell survival factors, such as B lymphocyte stimulator, produced by dendritic cells. Therefore, it is not surprising that the loss of expression of the type I IFN receptor can have dramatic effects on the production of autoantibodies and on the clinical features of systemic autoimmune diseases such as systemic lupus erythematosus. The innate immune response recognises pathogens and sterile danger signals to generate effector cytokines, such as type I interferons (IFNs), with a high degree of sophistication. The May/June 2012 issue provides a series of reviews of the role of type I IFNs in regulating immune responses. Topics to be covered include the reason for the induction of IFNs, type I IFNs interactions with and regulation of target cells (e.g. T cells, B cells and Th10 cells) in the immune system, and the roles and mechanisms of IFNs in specific organs or diseases. The accompanying web focus presents links to related articles from across Nature Publishing Group to provide more background information about these proteins.